Physicochemical Characterization of Physical Mixture and Solid Dispersion of Diclofenac Potassium with Mannitol - Han, Yong (2017)
Diclofenac potassium is an anti-inflammatory agent classified as a class II drug as per the biopharmaceutical classification system (BCS). The poor dissolution rate of water-insoluble drugs is still a major problem confronting the pharmaceutical industry. There are several techniques to enhance the dissolution of poorly soluble drugs. Methods available include salt formation, micronization and addition of solvent or surface active agents. The objective of the present work is to improve the dissolution profile of diclofenac potassium by formation of a physical mixture and a solid dispersion with mannitol. The solid dispersion was prepared by solvent method using ethanol/water. As diclofenac potassium melts with decomposition, the compatibility study with mannitol was done with the acid form by differential scanning calorimetry (DSC). The dissolution properties and physicochemical properties of diclofenac potassium:mannitol physical mixture and solid dispersion were investigated by Powder X-ray Diffraction (PXRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and dissolution test. This study shows that the dissolution rate of diclofenac potassium can be enhanced considerably by formulating it with mannitol, as a physical mixture or as a solid dispersion although crystallinity was maintained.